Ergonomics Study in Shared Kitchen Design at Flats Type 18 m2 Case Study Dupak Bangunrejo Surabaya Flats - Dyan Agustin; Niniek Anggriani; Erwin Djuni (Nusantara Science and Technology Proceedings)
The kitchen is part of a house used as a place to cook. On the flats, especially type 18m2 kitchen presence is not in each occupancy because of limited land, but placed together in one location with a limited area called a shared kitchen. The presence of a shared kitchen is actually very important in flats, but construction did not pay attention to the rules of ergonomics and comfort user's perception of working in the kitchen. As a result, it sometimes leads to complaints during cooking, even some residents decline to use the shared kitchen for reasons of design and placement of the shared kitchen. Therefore, it requirestable'sheight adjustment when cooking with an ideal height of 10 cm below elbow height. This adjustment is expected to create a more ergonomic attitude in cooking activities. This study used a sample of 30 occupants of the towers using qualitative research method with a case study approach. The study found all the important variables related to the subject under study, in this case, is the size of the field work, circulation, and the height of the work tool. The results showed that the design of a shared kitchen that is used now by the inhabitants of the towers is less ergonomic with a high position table is too high and the placement tool supporting tools are not in place so that cooking can improve skeletal muscle complaints.